Humoral immune response to autologous blood transfusion in hip surgery: whole blood versus packed red cells and plasma - Tolksdorf, Bernd; Frietsch, Thomas; Quintel, Michael; Kirschfink, Michael; Becker, P.; Weiler-Lorentz, Arnulf (Vox sanguinis, 2001)
BACKGROUND AND OBJECTIVES: The immune response to the transfused autologous buffy coat content in whole blood has, to date, not been studied in detail. SUBJECTS AND METHODS: Patients undergoing hip arthroplasty were studied according to whether they received autologous whole blood (WB) (n = 30), autologous fresh-frozen plasma and buffy coat-poor red cells (RC) (n = 40), or no transfusion (NT) (n = 27). Plasma levels of tumour necrosis factor-alpha (TNF-alpha), interleukin-6 (IL-6) and complement SC5b-9 were analysed by enzyme-linked immunosorbent assay (ELISA) 7 days after surgery. RESULTS: There were no significant between-group differences regarding the time course of TNF-alpha, IL-6 and complement SC5b-9 plasma level changes, the infection rate, or the length of hospital stay. CONCLUSION: In comparison to the impact of surgery on cytokine and complement levels, the transfusion of autologous buffy coat is not relevant.
First published: 28 July 2009
Gesehen am 15.02.2021